Figurative Language and the Five Main Values of Education Character in Indonesia in The Lyrics of Songs in Bon Jovi Album of Bon Jovi - Suryanto, Bradhiansyah Tri (Journal of ELT, Linguistics, and Literature, 2018)
Figurative language may involve analogy to similar concepts or other contexts, and may involve exaggerations. It also places greater emphasis on imaginative and creative meaning than literal meaning. Moreover, it is able to create mental images or express experience in the mind. And it is concerned with metaphorical meaning. In other side, education character that can shape good identity of someone, people, or a nation becomes substantial part in developing better generation in nowadays life. The values in education character in Indonesia which were contained in the literary works, especially lyric of songs become interesting to be studied. This study aims to analyze rhetorical devices in the words, phrases, sentences in the lyrics of songs in Bon Jovi album of Bon Jovi and to find out kinds of figurative language used in the lyrics and its values in term of the values in education character in Indonesia based on Perpres Nomor 87 Tahun 2017. There are nine lyrics were analyzed using descriptive approach. To avoid the different interpretation, this study used the classification of Figurative Language by M.H. Abram (1999). The result obtained there are nine kinds of figurative language found out that consisted of the five main values of education character in Indonesia. They are epithets, euphemism, hyperbole, irony, metaphor, personification, simile, symbol, and synecdoche with the character education values are